Virtual Interview Preparation for Generation Z Science, Technology, Engineering, and Math (STEM) Students - A Necessity for the Post-Pandemic Era: A Gen Z STEM Student Virtual Interview Step-by-Step Guide - Mahayosnand, Ponn P.; Sabra, SM (GILE Journal of Skills Development, 2023)
Social distancing and remote work were mandated worldwide during the COVID-19 lockdown. While virtual interviews were conducted prior to lockdown due to the growing global workforce, they became normalized during the pandemic for both work and school. Hiring agents may believe that having grown up with technology and the internet Generation Z (Gen Z) may be well-prepared for virtual interviews. However, the challenge they face is not technology-related. Gen Z individuals, particularly those in STEM fields, often lack well-developed practical and pragmatic life skills, such as effective communication. A remote independent research scholar and her student compiled this field report. First, the general characteristics of Gen Z STEM students are presented, followed by a virtual interview preparation guide with tips, recommendations and examples. Given the ever-changing global remote workforce, future empirical studies are recommended on the virtual hiring process of Gen Z STEM students which includes and expands upon virtual interviews.